PENGARUH STRATEGI SELF TALK TERHADAP KEMAMPUAN LOMPAT TINGGI - Asnani, Agata Afra; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study whether the high jump ability of students is still not maximal and lacks the courage to do high jump?. This study aims to determine whether there is an effect of self talk strstegies on high jump ability in class X students of Pontianak Maranatha Christian High School. The method used is the experimental method using the design technique â€œPretest-Posttest Control Group Designâ€. Data collection tool uses the high jump capability and RPP instrument. The data analysis tecnique used in this study uses the analysis prerequisite in the form of normality test, homogenety test and hypothesis test. The population in this study were students of class X, amounting to 56 people from 2 classes X Maranatha Christian High School Pontianak then sampling in this study using purposive sampling technique with a toal of 10 people. The results showed that the effect of self talk strategies was significant on high jump ability in students where the posttest average was 17.2, which was meant as a good category and the average pretest results were 13.9 which included poor categories with a t hitung valube (7.359) > t table (2,262). Then the hypothesis Ho is rejected and Ha is accepted, that is, there is the effect of Self Talk Strategy on High Jump Ability in Class X Maranatha Christian High School Pontianak.Â Â Keywords:Â Â Â Â Â Â  Self Talk, High Jump